Peran Good Corporate Governance (GCG) Dalam Optimalisas Layanan Mustahik Zakat Di Dompet Dhuafa Palembang - Fitriyada; Rinol Sumantri; Iceu Sri Gustiana (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
"Lamusta" is an activities oriented towards serving and consulting on community issues with a Dawah approach, aiming to provide contributions and solutions to the issues faced by recipients (recipient) and to create programs that enhance the dignity and well-being of the underprivileged. This research aims to analyze the implementation of Good Corporate Governance (GCG) in optimizing zakat services for Mustahik in Dompet Duafa Palembang, South Sumatra. The research methodology used for this study is a qualitative approach, employing techniques such as interviews, documentation, and observation. The findings of this research reveal that the of Good Corporate Governance (GCG) in the optimization of zakat services is not yet optimal, primarily due to a lack of promptness in providing assistance to beneficiaries (Mustahik). Furthermore, the human resources responsible for conducting surveys and delivering aid are identified as inhibiting factors. It is hoped that the role of Good Corporate Governance (GCG) can be improved in the future, particularly in terms of responsiveness.